Reframing the Spirit of Gender Equality: a Prototype of Woman Religious Leader in Pesantren Nahdlatul Ulama - Muhamad Rozikan (Journal of Nahdlatul Ulama Studies, 2022)
Gender in pesantren is a unique socio-cultural phenomenon because the patriarchal culture is still very strong in dominating. This culture is constructed by a social system in which men hold primary power and predominate in leadership, authority, and social privilege. The role of the Kyai as a central figure is considered in participating in the practice of gender bias and patriarchal culture. Therefore, the figure of Nyai is often positioned as a companion who has no strong power in designing the education system in pesantren. This research exposes the role of a woman leader in internalizing the spirit of gender equality. Since 2015, Nyai Latifah has emerged in leading pesantren Nadhlatul Ulama Tarbiyatul Islam Al-Falah Salatiga with 404 students which consist of 150 male and 254 female students. Her existence as the top authority in this pesantren shows woman empowerment who can change the tradition of social construction, which states that women do not have the capability to be a leader in pesantren. The results showed that Nyai Latifah's leadership pattern had reformed the pesantren system from a patriarchal leadership pattern to a gender mainstreaming leadership, viewed from Gender Analysis Pathway. The process of gender mainstreaming is realized through curriculum, learning activities, and organizational systems. In addition, the spirit of gender equality developed by Nyai Latifah in this pesantren is reflected in the principle of equality (musawamah), fairness (al-‘adalah), moderation (tawasut), tolerance (tasamuh), balance (tawazun), plurality (ta’addud), and respect (al ihtiram). Keywords: gender equality, woman, leader, pesantren